IRT analysis of the BDI-II for early online depression detection: validation in a Mexican population - Salcedo-Callado, Tonathiu; Hernández-Llanes, Norberto; Sánchez-Domínguez, Ricardo; Saracco-Alvarez, Ricardo; Marín-Navarrete, Rodrigo (Frontiers in Psychology, 2025)
IntroductionIdentifying factors associated with depression is crucial to addressing the global rise in mental health needs. The Beck Depression Inventory II (BDI-II) has shown robustness in assessing depression, even in digital contexts. However, psychometric evidence is essential to support its use in online self-diagnosis, particularly in regions where it has not been widely employed for this purpose.ObjectiveThis study aimed to evaluate the psychometric properties of the BDI-II for online self-diagnosis among Mexican adults.MethodData from 58,456 medical records were analysed using Item Response Theory (IRT).ResultsA good fit was found for a hierarchical confirmatory model with 1 s-order factor (overall severity) and two first-order factors (cognitive and somatic symptoms), as well as optimal accuracy estimates in both the IRT and the Classical Test Theory (CTT).DiscussionThese findings support the use of the BDI-II as a reliable online screening tool for depression in self-diagnosis settings for Mexican adults.